Oocyte retrieval difficulties in women with ovarian endometriomas. Issue 1 (July 2018) - Benaglia, Laura; Busnelli, Andrea; Biancardi, Rossella; Vegetti, Walter; Reschini, Marco; Vercellini, Paolo; Somigliana, Edgardo
Abstract: Research question: What are the frequency, characteristics and consequences of technical diffiiculties encountered by physicians when carrying out oocyte retrieval in women with ovarian endometriomas? Design: We prospectively recruited women undergoing IVF and compared technical difficulties between women with ( n = 56) and without ( n = 227) endometriomas. Results: In exposed women, the cyst had to be transfixed in eight cases (14%, 95% CI 7 to 25%) and accidental contamination of the follicular fluid with the endometrioma content was recorded in nine women (16%, 95% CI 8 to 27%). Moreover, follicular aspiration was more frequently incomplete (OR 3.6, 95% CI 1.4 to 9.6). In contrast, the retrievals were not deemed to be more technically difficult by the physicians and the rate of oocytes retrieved per developed follicle did not differ. No pelvic infections or cyst ruptures were recorded (0%, 95% CI 0 to 5%). Conclusions: Oocyte retrieval in women with ovarian endometriomas is more problematic but the magnitude of these increased difficulties is modest.